Endogenous Home Bias in Portfolio Diversification and Firms Entry. - Arespa-Castelló, Marta (John Wiley & Sons Ltd, 2014)
The home bias in portfolios is considered a main puzzle in international macroeconomics. This paper pro- vides a new benchmark for its analysis in a tractable new open economy macroeconomic model, where the home-biased position is an optimal allocation. An equilibrium model of perfect risk-sharing is specified, with endogenous portfolios and firm entry. Unlike in previous work, the international portfolio diversifica- tion is driven by home bias in capital goods—independently of home bias in consumption when countries are of equal size. The model explains the recent patterns of portfolio allocations in developed economies. Most important, optimal portfolio shares are independent of market dynamics.
Keywords: Macroeconomía; Inversiones; Home bias; Portfolio diversification; Monopolistic competition; Firm's entry; Macroeconomic puzzle